Performance Analysis of an IoT-Based Smart Energy Meter for Real-Time Monitoring of Electrical Energy Consumption - Farid Farid; Dewi Humeira Amriah; Muhammad Fathur Rahman Nur; Nurfitri Nurfitri; Muh. Erdin (Universitas Islam Raden Rahmat, Malang, 2026)
This study presents the performance analysis of an IoT-based Smart Energy Meter designed for real-time monitoring of electrical energy consumption. The system utilizes a NodeMCU ESP8266 microcontroller integrated with two PZEM-004T modules and PZCT-02 current sensors to measure voltage, current, power, and energy from multiple electrical loads. The measured data is transmitted to the Blynk platform, enabling real-time monitoring through a smartphone application. The performance of the system was evaluated by comparing the measurement results with a standard multimeter, resulting in average errors of 0.447% for voltage, 1.704% for current, and 1.844% for power, indicating good measurement accuracy. Experimental results under different load conditions show that higher power loads lead to significantly increased energy consumption and operational cost, where a 32 W load consumes approximately 0.038 kWh compared to 0.006 kWh for a 5 W load within the same duration. Overall, the system demonstrates reliable performance and provides an effective solution for real-time energy monitoring and management in household applications.